The Role of Diffusion-Tensor Magnetic Resonance Imaging and Tractography in the Diagnosis of Structural Brain Disorders in Children with Cerebral Palsy - Yu. V. Ermolina; L. S. Namazova-Baranova; A. M. Mamedyarov; A. V. Anikin; O. I. Maslova (Вопросы современной педиатрии)
In the past few decades, the active introduction of neuroimaging methods into clinical practice and research allowed us to assess the in vivo structural and functional state of the nervous system in children of all ages, from prenatal period of the development. The data obtained during neuroimaging studies significantly complemented the traditional view, based on the application of classical morphological methods. Using diffusion-tensor magnetic resonance imaging and tractography, it became possible to conduct comprehensive structural and functional studies, to study the main stages of the brain maturation in dynamics, and to compare the morphological data with peculiarities of psycho-verbal and motor development of a child, as well as to conduct clinical and neuroimaging comparison. The article describes modern possibilities of diagnostics of microstructural damages of the brain using diffusion-tensor tractography in children with post-hypoxic conditions and cerebral palsy. It is shown that the revealed changes correlate with aspect of the disease.